Grassland trees and the common bulbul Pycnonotus barbatus promote Afromontane forest restoration. (28th June 2021) - Jaafar, Ridwan; Yadok, Biplang G.; Elisha, Emmanuel B.; Chapman, Hazel M.
Abstract: Restoration of Afromontane forests is critical because of their biodiversity richness and ecosystem service provision. With an evolutionary history of rapid forest migration into grassland in response to shifting climate, traits of Afromontane forests such as a high frequency of light tolerant, small fruited, and bird dispersed species may pre‐adapt them to relatively rapid recolonization of grassland protected from fire. Here, we test this hypothesis with a focus on the role of isolated grassland tree species in promoting forest regeneration. Through seed, seedling, and frugivore surveys, we found that seed rain below small, isolated grassland trees was almost 300 times that in open grassland, with 30 times more seedlings established under trees. However, these seedlings were mostly grassland or forest edge woody shrubs or small trees. Dispersal limitation was moderate to high and establishment limitation high for all other species. Ecological filtering of seed species favored some over others, which needs further exploration. Key tree traits attracting frugivore visits were distance from forest edge, height, and "leaflessness." Across a year of sampling almost 90% of frugivore visits to isolated trees were by just two grassland / forest edge species, the common bulbul Pycnonotus barbatus (71%) and the speckled mouse bird Colius striatus (17%). Overall, our results suggest that while anthropogenic changes within Afromontane systems render any pre‐adaption Afromontane forests may have to rapid reestablishment of forest into grassland ineffectual, small, isolated grassland trees are nevertheless critical for the first stage of succession. Abstract : We tested the hypothesis that Afromontane forests are pre‐adapted to rapidly regenerate into grasslands. On the contrary, we found extreme dispersal and establishment limitation of tree species in grassland. One species, the common bulbul (Pycnonotus barbatus) is responsible for vast majority of seeds dispersed.